2009
DOI: 10.1111/j.1365-2958.2009.06917.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional stratification of the Spitzenkörper of Neurospora crassa

Abstract: SummaryGS-1 (ncu04189) is a protein required for the synthesis of b-1,3-glucan in Neurospora crassa. As chitin, b-1,3-glucan is a morphogenetically relevant component of the fungal cell wall. Previously, we showed that chitin synthases are delivered to the growing hyphal tip of N. crassa by secretory microvesicles that follow an unconventional route and accumulate in the core of the Spitzenkörper (Spk). Tagged with the green fluorescent protein (GFP), GS-1 accumulated in the hyphal apex forming a dynamic and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(116 citation statements)
references
References 44 publications
5
110
1
Order By: Relevance
“…Even though PMA-1-GFP was found in cell fractions of a density corresponding to that of ER and macrovesicles (35), it did not accumulate at the Spitzenkörper, where there is the highest concentration of secretory vesicles according to electron micrographs of hyphal tips of N. crassa (36). Instead, PMA-1-GFP localizes in subapical regions and is somehow directly delivered to the PM.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Even though PMA-1-GFP was found in cell fractions of a density corresponding to that of ER and macrovesicles (35), it did not accumulate at the Spitzenkörper, where there is the highest concentration of secretory vesicles according to electron micrographs of hyphal tips of N. crassa (36). Instead, PMA-1-GFP localizes in subapical regions and is somehow directly delivered to the PM.…”
Section: Discussionmentioning
confidence: 96%
“…S4A and B), corresponding to 1.155 and 1.158 g/ml. This indicated that PMA-1 travels in high-density vesicles and is found at the PM (34,35).…”
Section: Selection Of Strains Expressing Pma-1-gfpmentioning
confidence: 99%
“…Standard PCR and cloning procedures were used to fuse green fluorescent protein (GFP) and mCherry fluorescent protein (mChFP) N terminally using plasmids pCCG::N-GFP and pJV16-N, respectively, for targeted integration into the his-3 locus of N. crassa strain FGSC 9717 (33,34). The full-length 5.77-kb open reading frame (ORF) of nkin2 (kinesin-3; NCU06733) was amplified by PCR from FGSC 9717 genomic DNA using primers Nkin2_PacI_fwd (5=-CTTAATTAACAT GGCTCCAGGCATGGC-3=) and Nkin2_XbaI_rev (5=-GCTCTAGATCA AAACCTCAACTGACTG-3=), which included PacI and XbaI restriction sites (which are underlined).…”
Section: Methodsmentioning
confidence: 99%
“…This generally correlates with an increase in the rate of apical extension (Horio and Oakley 2005), as well as the appearance of a Spitzenkörper (apical body). The latter structure is typically located proximal to the hyphal tip (Girbardt 1957;Sudbery 2011a), largely composed of vesicles of different sizes, microfilaments, and ribosomes (Harris et al 2005;Verdin et al 2009). An extensive body of data support the view that Spitzenkörper dynamics determine the shape of the hyphal tip, dictate the orientation of hyphal extension (BartnickiGarcia et al 1995;Riquelme 2013), and help maximize rates of apical extension (Kohli et al 2008).…”
Section: Hyphal Morphogenesismentioning
confidence: 99%